2013
DOI: 10.1523/jneurosci.0449-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

Decoding the Neuroanatomical Basis of Reading Ability: A Multivoxel Morphometric Study

Abstract: As a relatively recent cultural invention in human evolution, reading is an important gateway to personal development and socioeconomic success. Despite the well documented individual differences in reading ability, its neuroanatomical correlates have not been well understood, largely due to the fact that reading is a complex skill that consists of multiple components. Using a large sample of 416 college students and 7 reading tasks, the present study successfully identified three uncorrelated components of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
75
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(92 citation statements)
references
References 79 publications
13
75
4
Order By: Relevance
“…Whereas better readers on average exhibited volume reductions, poor readers on average exhibited volume growth in these areas. These findings seem inconsistent with previous findings of positive correlations between measures of cortical volume and reading proficiency in left inferior parietal regions, as reported by some of the studies cited above (i.e., He et al, 2013;Blackmon et al, 2010). Furthermore, the only previous study that reports volume changes directly related to reading acquisition found higher gray matter density in temporoparietal regions in persons who acquired literacy as adults when compared with illiterate adults (Carreiras et al, 2009).…”
Section: Discussioncontrasting
confidence: 94%
See 3 more Smart Citations
“…Whereas better readers on average exhibited volume reductions, poor readers on average exhibited volume growth in these areas. These findings seem inconsistent with previous findings of positive correlations between measures of cortical volume and reading proficiency in left inferior parietal regions, as reported by some of the studies cited above (i.e., He et al, 2013;Blackmon et al, 2010). Furthermore, the only previous study that reports volume changes directly related to reading acquisition found higher gray matter density in temporoparietal regions in persons who acquired literacy as adults when compared with illiterate adults (Carreiras et al, 2009).…”
Section: Discussioncontrasting
confidence: 94%
“…In contrast to these studies, no association between gray matter volume at baseline or follow-up measurement and reading proficiency at the respective (or the following) measurement time point could be found in this study. However, intraindividual changes in reading proficiency between the two measurement time points were positively related to baseline gray matter volume in the superior temporal gyrus, including parts of the planum temporale, that is, similar areas as reported by some of the studies cited above (i.e., He et al, 2013;Blackmon et al, 2010;Steinbrink et al, 2008). Furthermore, it resonates with studies reporting neurostructural differences between normal reading participants and participants suffering from developmental dyslexia, a specific impairment affecting the acquisition of reading skills.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Although neuropsychological studies such as Broca's have been valuable, technological advances in neuroimaging have drastically expanded the types of questions we can ask about cognition, especially in the healthy brain. For example, neuroimaging techniques have uncovered and refined theories about brain areas being "dedicated" to some domains of cognition, such as face processing (Kanwisher, McDermott, & Chun, 1997), phonological decoding (Boukrina, Barrett, Alexander, Yao, & Graves, 2015;He at al., 2013,), and the planning of motor speech (Dronkers, 1996;Richardson, Fillmore, Rorden, LaPointe, & Fridriksson, 2012).…”
Section: Introductionmentioning
confidence: 99%